Temporal analysis of COVID-19 maternal mortality in Brazil in 2022 and 2023: cross-sectional study (Revista Científica Integrada, 2025)
Objective: To analyze the mortality and clinical evolution of women of reproductive age (pregnant and postpartum women) with COVID-19 in Brazil during the years 2022 and 2023. Method: This is a cross-sectional, descriptive and exploratory study based on secondary data from the Brazilian Obstetric Observatory on COVID-19 (OOBr). Records of hospitalized women diagnosed with COVID-19 were included, covering demographic, clinical and gestational information. The analyses involved descriptive and bivariate statistics, considering a significance level of p
Keywords: COVID-19; Pregnancy; Postpartum period; Women's health; Maternal mortality